The overlooked role of reduced graphene oxide in the reinforcement of hydrophilic polymers1. Issue 6 (14th February 2015) - Flores, A.; Salavagione, H. J.; Ania, F.; Martínez, G.; Ellis, G.; Gómez-Fatou, M. A.
<x xml:space="preserve">Abstract</x> Mechanical properties of PVA are stabilized against moisture absorption by highly hydrophobic graphene.